Belowground Defence Strategies in Plants - Vos, Christine M.F; Kazan, Kemal (Signaling and Communication in Plants, 2016)
This book summarizes our current knowledge on belowground defence strategies in plants by world-class scientists actively working in the area. The volume includes chapters covering belowground defence to main soil pathogens such as Fusarium, Rhizoctonia, Verticillium, Phytophthora, Pythium and Plasmodiophora, as well as to migratory and sedentary plant parasitic nematodes. In addition, the role of root exudates in belowground plant defence will be highlighted. Finally, accumulating evidence on how plants can differentiate beneficial soil microbes from the pathogenic ones will be covered as well. This will be further highlighted in chapters covering the plant responses to beneficial micro-organisms such as non-pathogenic Fusarium, Trichoderma, Piriformospora and arbuscular mycorrhizal fungi. Better understanding of belowground defences can lead to the development of environmentally friendly plant protection strategies effective against soil-borne pathogens which cause substantial damage on many crop plants all over the world. The book will be a useful reference for plant pathologists, agronomists, plant molecular biologists as well as students working on these and related areas.